PROSES PERANCANGAN PROGRAM ACARA PADA RAPAT KOORDINASI MICE 2018 OLEH KEMENTERIAN PARIWISATA REPUBLIK INDONESIA - Anugrah Syiamoe Akbar; Tuty Herawati (Bisnis Event, 2020)
Like other government agencies, MICE activities are a type of activity that is very often carried out in the Ministry of Tourism. The MICE 2018 Coordination Meeting is one form of activity to drive the motivation of MICE industry stakeholders to jointly encourage the acceleration of Indonesia as a competitive MICE destination. One of the basic successes in organizing this activity is the conveying of the message meant through the program that was compiled. In designing programs that are in the implementation of activities. The Ministry of Tourism has its own rules and procedures in the preparation process for matters relating to the implementation of activities. In addition, everything that has been planned must also be coordinated and approved by the leaders within the Ministry of Tourism. This study aims to understand the importance of preparing an event program well so that the message to be conveyed to the participants of the activity can be well and clearly received. The method used in this research is descriptive qualitative, through observation and experience gained during the preparation process.